1998
DOI: 10.1103/physrevlett.80.2801
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of3Heby Spin Exchange with Optically Pumped Rb and K Vapors

Abstract: We report on extensive experimental measurements of the key rates that determine the efficiency for polarizing the nuclei of 3 He by spin exchange with optically pumped Rb vapor. In agreement with recent theoretical predictions, we find a strong temperature dependence of the electron-spin loss rates due to 3 HeRb collisions. We also find that the maximum possible efficiency for spin-exchange polarization of 3 He by K is 10 times greater than for Rb. [S0031-9007(98)05659-2]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(45 citation statements)
references
References 21 publications
5
39
1
Order By: Relevance
“…atoms Rb or K see, e.g., Refs. 7,8 and x Ž . references cited therein or b by optical pump- alkali-metal atoms 9᎐11 .…”
Section: Optical Pumping and Spin Exchange: Basic Principlesmentioning
confidence: 99%
“…atoms Rb or K see, e.g., Refs. 7,8 and x Ž . references cited therein or b by optical pump- alkali-metal atoms 9᎐11 .…”
Section: Optical Pumping and Spin Exchange: Basic Principlesmentioning
confidence: 99%
“…A pure Rb vapor was used to polarize 3 He prior to the development of hybrid cells. However, it was found that K is far more efficient than Rb at transferring its polarization to 3 He nuclei [37]. Hybrid mixtures of Rb and K have subsequently been used to improve the efficiency of the polarization process [37,50,51].…”
Section: Development Of Hybrid Targetsmentioning
confidence: 99%
“…However, it was found that K is far more efficient than Rb at transferring its polarization to 3 He nuclei [37]. Hybrid mixtures of Rb and K have subsequently been used to improve the efficiency of the polarization process [37,50,51]. In alkali-hybrid spin-exchange optical pumping (AHSEOP), the Rb vapor is polarized by circularly polarized laser light, but the polarization of Rb valence electrons is then rapidly shared with the K [29].…”
Section: Development Of Hybrid Targetsmentioning
confidence: 99%
“…and the spin-exchange rate constant for helium-rubidium has been measured to be κ se = 6.7 ± 0.610 −20 cm 3 /s [46]. At the operating temperatures of helium-3 SEOP polarizers utilizing rubidium alone (T ∼ 190 • C), [Rb] ≈ 6.2 * 10 14 atoms/cm 3 and γ se ≈ 1 6.7 hours.…”
Section: Spin-exchange Optical Pumpingmentioning
confidence: 99%